2016
DOI: 10.2188/jea.je20150040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Public Education Campaign on the Association Between Knowledge of Early Stroke Symptoms and Intention to Call an Ambulance at Stroke Onset: The Acquisition of Stroke Knowledge (ASK) Study

Abstract: BackgroundAn immediate ambulance call offers the greatest opportunity for acute stroke therapy. Effectively using ambulance services requires strengthening the association between knowledge of early stroke symptoms and intention to call an ambulance at stroke onset, and encouraging the public to use ambulance services.MethodsThe present study utilized data from the Acquisition of Stroke Knowledge (ASK) study, which administered multiple-choice, mail-in surveys regarding awareness of early stroke symptoms and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
2
7
0
3
Order By: Relevance
“…34 Therefore, comprehensive SK concepts may need to include issues over one's entire life course 35 and encompass the epidemiology, risk factors, warning signs, emergency response, symptoms, and treatment/ rehabilitation of stroke, as well as concepts relevant to the long-term care, disability prevention, and health promotion. 36 Because SK covers multidimensional concepts across the continuum of stroke management, the framework proposed by the European Commission has the potential to be the basis for validating current SK tests and developing or refining additional tests.…”
Section: Discussionmentioning
confidence: 99%
“…34 Therefore, comprehensive SK concepts may need to include issues over one's entire life course 35 and encompass the epidemiology, risk factors, warning signs, emergency response, symptoms, and treatment/ rehabilitation of stroke, as well as concepts relevant to the long-term care, disability prevention, and health promotion. 36 Because SK covers multidimensional concepts across the continuum of stroke management, the framework proposed by the European Commission has the potential to be the basis for validating current SK tests and developing or refining additional tests.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that GPs tend to have a lower prediction level of stroke than paramedics and EMS physicians. Nishikawa et al found an increased association between stroke symptom knowledge and intention to call an ambulance after a 2 year long stroke education campaign in Japan. A 2015 systematic review on stroke warning campaign studies found that although a majority reported positive intervention effects, the generalizability were limited because of methodological weaknesses.…”
Section: Discussionmentioning
confidence: 99%
“…Téměř všechny tyto kampaně se zaměřovaly obecně na dospělou populaci. V některých případech [4,5,21,22,24,27,28] ovšem studie hodnotily vliv kampaní v některých vybraných věkových skupinách. Tři studie [25,30,31] jsou školní programy zaměřené na děti a dvě [32,34] zahrnují i rodiče těchto dětí.…”
Section: Uspořádání Vzdělávacích Kampaníunclassified